1998
DOI: 10.1046/j.1471-4159.1998.70062336.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Responsiveness of Avian Cochlear Neurons to Brain‐Derived Neurotrophic Factor and Nerve Growth Factor by HSV‐1‐Mediated Gene Transfer

Abstract: : The importance of individual members of the neurotrophin gene family for avian inner ear development is not clearly defined. Here we address the role of two neurotrophins, brain‐derived neurotrophic factor (BDNF) and nerve growth factor (NGF), for innervation of the chicken cochlea. We have used defective herpes simplex virus type 1 (HSV‐1) vectors, or amplicons, to express these neurotrophins in dissociated cultures of cochlear neurons. HSV‐1‐mediated expression of BDNF promotes neuronal survival similar to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 8 publications
1
16
0
1
Order By: Relevance
“…They have been used to deliver neurotrophins, like nerve growth factor (NGF) 124,125 or brain-derived neurotrophic factor (BDNF), 124,126 antiapoptotic genes, 127,128 heat-shock proteins 129 or antioxidant enzymes, 130 in attempts to protect neurons against a variety of neurological insults, in many different experimental settings. Amplicons expressing genes affecting neurotransmitter expression or neuroreceptor synthesis have been used to study behavioral features, like learning and memory.…”
Section: Amplicon Vectorsmentioning
confidence: 99%
“…They have been used to deliver neurotrophins, like nerve growth factor (NGF) 124,125 or brain-derived neurotrophic factor (BDNF), 124,126 antiapoptotic genes, 127,128 heat-shock proteins 129 or antioxidant enzymes, 130 in attempts to protect neurons against a variety of neurological insults, in many different experimental settings. Amplicons expressing genes affecting neurotransmitter expression or neuroreceptor synthesis have been used to study behavioral features, like learning and memory.…”
Section: Amplicon Vectorsmentioning
confidence: 99%
“…Neurotrophin-3 (NT-3) and brain-derived neurotrophic factor (BDNF) are part of the NGF family of neurotrophic factors. NT-3 and BDNF are produced by the inner hair cells of the cochlea and exert their actions in an autocrine or paracrine fashion [Garrido et al, 1998]. If hair cells are destroyed by a toxic agent (e.g.…”
Section: Neurotrophin Withdrawal-induced Apoptosis Of Auditory Neuronsmentioning
confidence: 99%
“…The results of these gene-knockout studies indicate that NT-3 plays a major role, in concert with BDNF, in the development of the peripheral auditory system. Although the maximal responsiveness to NGF, BDNF or NT-3 is observed at around E7-13, these neurotrophins decrease with maturation (10,27). In situ studies showed that NGF and BDNF transcripts Table I).…”
Section: Discussionmentioning
confidence: 99%